Hubungan Minat Belajar dan Kedisiplinan Belajar dengan Keaktifan Belajar Siswa SD Negeri 23 Jeppe’e Kecamatan Tanete Riattang Barat Kabupaten Bone - Asrida Arma; Wahira; Amir Pada (Jurnal Pustaka Cendekia Pendidikan, 2025)
The formulation of the problem in this study is how is the picture of learning interest, learning discipline, learning activity of UPT SD Negeri 23 Jeppe'e, Tanete Riattang Barat District, Bone Regency? and is there a significant relationship between learning interest and learning discipline with learning activity of UPT SD Negeri 23 Jeppe'e, Tanete Riattang Barat District, Bone Regency? This study is a correlation study that aims to determine the picture of learning interest, learning discipline, learning activity and the relationship between learning interest and learning discipline with learning activity of UPT SD Negeri 23 Jeppe'e, Tanete Riattang Barat District, Bone Regency. The research approach is a quantitative approach. The research data were obtained through questionnaires and documentation. The population in the study were all high-grade students at UPT SD Negeri 23 Jeppe'e, Tanete Riattang Barat sub-district, Bone regency, totaling 30 students. The sample in the study was 30 students. The data analysis technique was descriptive and inferential statistical analysis. The results obtained in this study are a description of learning interest showing a very high category and learning discipline showing a very high category with learning activity showing a high category and learning interest and learning discipline have a significant relationship to student learning activity, especially in the high-grade UPT SD Negeri 23 Jeppe'e, Tanete Riattang Barat district, Bone regency.